Efficacy of compound sodium acetate Ringer’s solution in early fluid resuscitation for children with septic shock: a preliminary retrospective cohort study - Jiaqin Li; Min Nie; Ziwei Lu; Yinsu Wang; Xing Shen (BMC Pediatrics)
Abstract Background The effectiveness of acetated Ringer’s solution in pediatric shock has received little attention. This study aimed to assess the clinical outcomes of using compound sodium acetate Ringer’s solution (AR) for fluid resuscitation in children with septic shock. Methods We retrospectively analyzed the clinical data of children with septic shock admitted to the pediatric intensive care unit of the Affiliated Hospital of Southwest Medical University from December 2019 to January 2023. Based on the resuscitation fluid administered, the participants were categorized into the compound AR and normal saline (NS) groups. We compared blood circulation conditions, internal environment parameters (arterial blood pH, lactic acid, serum sodium, chloride, calcium, magnesium, potassium, and blood glucose), and 28-day clinical outcomes between the two groups. Results This study included 40 children, with 13 and 27 in the compound AR and NS groups, respectively. The two groups showed no significant differences in sex, age, body weight, body mass index, primary inflammation level, or Pediatric Sequential Organ Failure Assessment on admission. Similarly, no significant difference was observed in resuscitation fluid volume administered during the first hour (compound AR group: 250.00 mL [100.00, 390.00]; NS group: 250.00 mL [100.00, 500.00]). The total amount of crystalloid and colloid fluids administered within 24 h, vasoactive drug use, and blood pressure recovery post-resuscitation did not significantly differ between the groups. However, at 6 h post-resuscitation, the compound AR had considerably lower lactate level than the NS group (1.12 vs. 2.20 mmol/L). There were no significant differences in arterial blood pH, serum sodium, chloride, calcium, magnesium, potassium, and blood glucose levels between the groups. After treatment, in the compound AR group, 3 patients died, 2 improved, and 8 were cured. In the NS group, 7 patients died, 8 improved, and 12 were cured. The 28-day treatment outcomes (mortality rate, improvement rate, cure rate, or side effects) showed no significant differences between the groups. Conclusions Compound AR was as effective as NS as a resuscitation fluid in pediatric septic shock, demonstrating similar intravascular volume restoration and hemodynamic stability maintenance. However, it caused a faster decline in arterial lactate levels without obvious side effects.